ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN MAHASISWA DALAM MEMILIH JURUSAN PERBANKAN SYARIAH PADA FAKULTAS EKONOMI DAN BISNIS ISLAM - Irwansyah Irwansyah; Muhammad Subhan; Rabiyatul Alawiyah (CV. Aksara Global Akademia, 2023)
This research aims to look at the factors that influence students' decision making in choosing a Sharia Banking major at the Faculty of Economics and Islamic Business, UIN Sultan Thaha Saifuddin Jambi. This research uses quantitative methods, in this research uses personal and social variables. The population in this study was all 96 students from the class of 2022. The sample used was incidental sampling with a total sample of 49 students. This research uses multiple linear analysis, classical assumption test, t test and f test and uses the coefficient of determination (R2). Based on the results of partial research, it shows that personal and social variables have a significant influence on student decision making in choosing a Sharia Banking major. Simultaneously or together, personal and social variables have a significant influence on students' decision making in choosing a Sharia Banking major with a value of 0.723, which shows that decision making is influenced by 72% of independent variables and the remaining 28% is influenced by other variables not explained in this research. . It is hoped that from the results of this research, the banking study program can maintain personal and social variables which are the most dominant factors in influencing student decision making in choosing a Sharia Banking major, Faculty of Islamic Economics and Business, UIN Sultan Thaha Saifuddin Jambi.